REKONSTRUKSI MORALITAS BANGSA MENUJU MASYARAKAT MADANI (PERSPEKTIF DURKHEIMIAN) - Susilo, Rachmad K. Dwi (Jurnal Bestari, 2001)
One of social system elements as justification is morality. For New order government morality just has believed as integrity means for gain developmentgoal. Indigenous social system never has looked by honestly and objectively. But , all only serviced development targets. So , reform movement appearance has signed by spirit to change destructive to constructive morality. Reform movement has general commitment to reform nation morality.